Effect of temperature on circadian clock functioning of trees in the context of global warming - Estravis Barcala, Maximiliano (2025)
Plant survival in a warmer world requires the timely adjustment of biological processes to cyclical changes in the new environment. Circadian oscillators have been proposed to contribute to thermal adaptation and plasticity. However, the influence of temperature on circadian clock performance and its impact on plant behaviour in natural ecosystems are not well-understood. We combined bioinformatics, molecular biology and ecophysiology to investigate the effects of increasing temperatures on the functioning of the circadian clock in two closely related tree species from Patagonian forests that constitute examples of adaptation to different thermal environments based on their altitudinal profiles. Nothofagus pumilio, the species from colder environments, showed a major rearrangement of its transcriptome and reduced ability to maintain rhythmicity at high temperatures compared with Nothofagus obliqua, which inhabits warmer zones. In altitude-swap experiments, N. pumilio, but not N. obliqua, showed limited oscillator function in warmer zones of the forest, and reduced survival and growth. Our findings show that interspecific differences in the influence of temperature on circadian clock performance are associated with preferred thermal niches, and to thermal plasticity of seedlings in natural environments, highlighting the potential role of a resonating oscillator in ecological adaptation to a warming environment.